2010
DOI: 10.1159/000321988
|View full text |Cite
|
Sign up to set email alerts
|

Cervical and Ocular Vestibular Evoked Myogenic Potentials Are Sensitive to Stimulus Phase

Abstract: Sinusoidal forces with frequencies of 100 and 500 Hz and initial positive or negative polarities were delivered to the mastoids and Fz in normal subjects. We investigated whether the cVEMPs and oVEMPs evoked were sensitive to the polarity (phase) of vibration. With mastoid stimulation at 100 Hz, medial head acceleration produced cVEMPs with earlier latency (15.5 ms) than lateral acceleration (19.7 ms) and oVEMPs with later latency (13.8 ms) than lateral acceleration (10.6 ms). As the stimulus frequency increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…Responses can change polarity and/or latency with different sites of stimulation. The effects are much greater for taps and low frequency tone bursts, but are still present with 500 Hz stimuli (Cai et al, 2011). When delivered to the anterior forehead around the hairline, stimuli that begin with acceleration toward the skull (as with a standard tendon hammer tap) produce earlier responses than those that begin with acceleration away from the skull, but the effects for other midline sites differ (Govender and Colebatch, 2017, Govender and Colebatch, 2018).…”
Section: Optimal Stimulus Parameters: Bone-conducted (Bc) Stimulationmentioning
confidence: 99%
“…Responses can change polarity and/or latency with different sites of stimulation. The effects are much greater for taps and low frequency tone bursts, but are still present with 500 Hz stimuli (Cai et al, 2011). When delivered to the anterior forehead around the hairline, stimuli that begin with acceleration toward the skull (as with a standard tendon hammer tap) produce earlier responses than those that begin with acceleration away from the skull, but the effects for other midline sites differ (Govender and Colebatch, 2017, Govender and Colebatch, 2018).…”
Section: Optimal Stimulus Parameters: Bone-conducted (Bc) Stimulationmentioning
confidence: 99%
“…All of these stimuli, except for the outward tap, have been shown to evoke cVEMPs with typical positive-negative (i.e. p13-n23) polarity (Cai et al, 2011;Colebatch et al, 1994;Rosengren et al, 2009), while the outward tap produces a cVEMP with the opposite polarity (negative-positive) (Rosengren et al, 2009). We predicted that the single motor unit responses would mirror the surface responses and change with changing stimulus type.…”
Section: Introductionmentioning
confidence: 96%
“…The most common types of stimulus delivered by these vibrators to evoke cVEMPs are: sine waves, often at 500 Hz and sometimes delivered to the forehead near Fz (e.g. Cai et al, 2011;Manzari et al, 2010Manzari et al, , 2012; square waves, either delivered to the forehead (e.g. Taylor et al, 2011Taylor et al, , 2012 or inion (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous reports, they found a broad tuning curve with no clear best frequency. They suggest that this differs from the tuning studies by Todd et al (2008Todd et al ( , 2009a, Cai et al (2011), andZhang et al (2012) and explains the differences in frequency tuning of the OVEMP found among the studies. Burgess et al (2013) have emphasized that their tuning study made use of the initial negativity, the "n10" wave.…”
mentioning
confidence: 55%